Social network size, loneliness, physical functioning and depressive symptoms among older adults: Examining reciprocal associations in four waves of the Longitudinal Aging Study Amsterdam (LASA). (9th May 2021) - Domènech‐Abella, Joan; Mundó, Jordi; Switsers, Lise; van Tilburg, Theo; Fernández, Daniel; Aznar‐Lou, Ignacio
Abstract: Introduction: Previous research indicates that social isolation, loneliness, physical dysfunction and depressive symptoms are interrelated factors, little is known about the potential pathways among them. The aim of the study is to analyse simultaneously reciprocal relationships that could exist between the four factors to clarify potential mediation effects. Methods: Within a large representative sample of older people in the Longitudinal Aging Study Amsterdam (LASA), participants aged 75 and over were followed up over a period of 11 years (four waves). We tested cross‐lagged and autoregressive longitudinal associations of social network size, loneliness, physical functioning and depressive symptoms using structural equation modelling (SEM). Results: Several statistically significant cross‐lagged associations were found: decreasing physical functioning (Coef. = −0.03; p  < 0.05), as well as social network size (Coef. = −0.02; p  < 0.05), predicted higher levels of loneliness, which predicted an increase in depressive symptoms (Coef. = 0.17; p  < 0.05) and further reduction of social network (Coef. = −0.20; p  < 0.05). Decreasing physical functioning also predicted an increase in depressive symptoms (Coef. = −0.08; p  < 0.05). All autoregressive associations were statistically significant. Conclusion: Interventions focused on promoting social activities among older adults after negative life events, such as loss of social contacts or declining physical function, may alleviate feelings of loneliness and act as mental health protector. Key points: Decreasing physical functioning, as well as social network size, predicted higher levels of loneliness among older adults. Loneliness predicted an increase in depressive symptoms and further reduction of social network. Decreasing physical functioning also predicted an increase in depressive symptoms.